Creative inquiry : from ideation to implementation - Stewart, Mary, 1952- (State University of New York Press, 2021)
"Creative Inquiry introduces both undergraduate students and general readers to the exploratory mindset and hands-on skills essential to the cultivation and implementation of new ideas. Using active learning, this book combines concise explanations and real-world examples with engaging exercises for readers to complete. The writing style is conversational, yet substantial, and the examples given reflect a wide range of disciplines, from early aeronautics and linguistics to zoology. Creative Inquiry emphasizes the importance of direct experience, personal initiative, and the generation of new knowledge. Step by step, the exercises build the skills students need when they tackle the final self-designed Capstone project. Positioned at the end of major sections, five brief self-reflection papers are designed to help students assess their progress and revise their assignments. To encourage collaboration and strengthen metacognition, teams of three to six participants work together on these papers. This encourages an iterative mindset and provides extensive practice with writing. The appendix provides a lively and practical "Top Ten List" of writing strategies for students who need extra advice."--